Endovascular management of acute limb ischemia. (October 2013) - Sedghi, Yabiz; Collins, Tyrone J; White, Christopher J
Acute limb ischemia (ALI) is defined as a sudden decrease (<14 days) in limb perfusion causing a potential threat to limb viability. Endovascular treatment of ALI is an effective and appropriate primary treatment strategy in patients with a viable acutely ischemic limb due to a recent arterial occlusion. We present a case of acute limb ischemia and discuss percutaneous interventional treatment strategies including catheter-directed thrombolysis, rheolytic thrombectomy, and utilization of distal protection devices.